The Implementation of Project Based Learning Method in Building Creativity, Encouraging Learning Motivation and Improving Language Skills - Fitriany, Fitriany; Husda, Azizah (Faculty of Tarbiyah nad Teacher Training, 2024)
This study is aimed to elaborate how the implementation of Project-Based Learning Methodology in the classroom benefits the students in building their creativity, encouraging their learning motivation and improving their language skills. The study is qualitative research with experiential approach. The study described the teachers and students point of view on the implementation of Project-Based Learning in their classroom. he implementation is not restricted to language/English subject but other subjects as well. In terms of language skills, the Project-Based Learning method has opened new ways to improve students’ speaking, writing, listening and reading skills. In creativity, Project-Based Learning encourages students to be creative, sharpens the critical thinking skill and interpersonal skill since the projects are mostly conducted in groups. PBL assist the poor academic students to have motivation to improve their academic achievements.